Concentration of human pollution tracers with ionic liquids - Dinis, Teresa Beatriz Vide (2018)
The main objective of the present thesis consists on the development of an analytical preconcentration technology for the concomitant extraction and concentration of human pollution tracers from wastewater streams. Due to the outstanding tunable properties of ionic liquids (ILs), aqueous biphasic systems (ABS) composed of ILs can provide higher and more selective extraction efficiencies for a wide range of compounds, being thus a promising alternative to the volatile and hazardous organic solvents (VOCs) typically used. For that purpose, IL-based ABS were employed and adequately characterized as an one-step extraction and concentration technique. The applicability of IL-based ABS was verified by their potential to completely extract and concentrate two representative pharmaceutical pollution tracers, namely caffeine (CAF) and carbamazepine (CBZ), from wastewaters. The low concentration of these persistent pollutants (usually found in μg·dm-3 and ng·dm-3 levels, respectively) by conventional analytical equipment does not permit a proper detection and quantification without a previous concentration step. Preconcentration methods commonly applied are costly, timeconsuming, with irregular recoveries and make use of VOCs. In this work, the ABS composed of the IL tetrabutylammonium chloride ([N4444]Cl) and the salt potassium citrate (K3[C6H5O7]) was investigated while demonstrating to be able to completely extract and concentrate CAF and CBZ, in a single-step, overcoming thus the detection limit of the applied analytical equipment. Finally, the hydrotropic effect responsible for the ability of IL-based ABS to extract and concentrate a wide variety of compounds was also investigated. It was shown that the IL rules the hydrotropic mechanism in the solubility of CAF in aqueous solutions, with an increase in solubility up to 4-fold. Moreover, the proper selection of the IL enables the design of the system that leads to a more enhanced solubility of a given solute in the IL-rich phase, while allowing a better extraction and concentration. IL-based ABS are a promising and more versatile technique, and are straightforwardly envisaged as selective extraction and concentration routes of target micropollutants from wastewater matrices.